1-2-3 draw knights, castles, and dragons : a step by step guide - Levin, Freddie ([Columbus, N.C.] : Peel Productions ; Cincinnati, OH : Distributed in North America by North Light Books, 2001)
An illustrated, step-by-step guide to drawing dragons, knights, weapons, castles, heraldry, and other symbols and inhabitants of an imaginary medieval world.
Includes index.
School Library Journal
4.6
3-6
Keywords: Knights and knighthood in art -- Juvenile literature; Dragons in art -- Juvenile literature; Castles in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Knights and knighthood in art; Dragons in art; Castles in art; Drawing -- Technique; Knights and knighthood; Dragons; Castles; Drawing -- Technique